back to *algebra2 video lessons*
# Transformation of the graph of a quadratic function

Question:

How to move the graph of y = 2x^{2} to get the graph of y = 2x^{2} + 12x + 17?

Solution:

Write the function y = 2x^{2} into the vertex form.

y = 2x^{2} = 2(x - 0)^{2} + 0

The vertex of the graph of y = 2x^{2} is (0, 0), axis of symmetry is x = 0 which is y-axis. Because the coefficient of the x square term is positive, so the graph is open upward.

Use the completing square formula to find the vertex of the quadratic function y = 2x^{2} + 12x + 17

y = 2x^{2} + 12x + 17 = 2(x^{2} + 6x) + 17 = 2(x^{2} + 6x + 3^{3} - 3^{3}) + 17 = 2(x^{2} + 6x + 3^{2}) - 18 + 17 = 2(x + 3)^{2} - 1

Therefore, vertex of the graph of the function y = 2x^{2} + 12x + 17 is (-3, -1), axis of symmetry is x = -3, and the graph is upward.

So, we need to move the graph of y = 2x^{2} left 3 units then down 1 unit to get the graph of y = 2x^{2} + 12x + 17.